CLINICAL CHARACTERISTICS OF CHILDREN WITH COVID-19 - Prijić, Andreja (Medicinski podmladak, 2023)
Covid-19 is a disease caused by the SARS-CoV-2 virus, which was registered in December 2019 in China. In February 2020, the World Health Organization declared the SARS-CoV-2 pandemic. The first pediatric patient in Serbia with covid-19 was registered on March 23, 2020, in the 13th week since the start of the pandemic. This disease, three years after the appearance of the first cases, continues to be a global public health challenge. Children get sick with covid-19 less often than adults. They are mostly infected by droplets in the household from family members, and they have a milder clinical picture and a better prognosis of the disease. The most common symptoms and signs of covid-19 in children are fever, cough, tachycardia and malaise. In  the first waves of the pandemic, pneumonia had about a quarter to a third of the patients. The indiscriminate use of antibiotics in the treatment of sick children was one of the main problems during the pandemic. Considering that the covid-19 infection was a threat of global proportions, in addition to the impact on the health condition, the deterioration of the quality of life of children was also registered.
Keywords: COVID-19; SARS-COV-2; coronavirus; clinical presentation; antiobiotic treatment